Замкнутая система активного экранирования магнитного поля вблизи токопроводов электростанций - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Бовдуй, Игорь Валентинович; Волошко, Александр Валерьевич; Виниченко, Елена Владимировна; Котляров, Денис Александрович (НТУ "ХПИ", 2013)
Magnetism of Technical Objects Science and Technology Center of the National Academy of Sciences of Ukraine are made physical models closed system of the active screening of magnetic field on the job position near the power stations bus. In the area of compensation of distortion of magnetic field the guided sources are placed of magnetic field, oriented in space definitely. The prototyping closed system of the active screening consists of five compensative puttees, engulfing job position and forming a compensating magnetic field. Results of experimental researches of efficiency of closed system of the active screening of magnetic field on the job position near the power stations bus is given.
Keywords: энергонасыщенные объекты; экологические нормы рабочих помещений; компенсирующее магнитное поле; макет замкнутой системы экранирования; индукция магнитного поля; компенсационные обмотки